The Process of Inheritace Ayu Mask Dance in Tanon Backwoods - Purwati, Anik; Malarsih, Malarsih; Cahyono, Agus (Universitas Negeri Semarang, 2019)
This study aims to analyze the process of inheritance in Hamlet Tanon, especially the Mask Dance Ayu as a result of culture. This study uses the approach of cultural sociology. The data collection is done in three ways: observation, interview and documentation. The validity of the data using triangulation techniques and reviews of informants, with interactive data analysis. The results of the research that Inheritance Mask Dance Ayu in the Hamlet Tanon using nyantrik with imitation technique, where children make the observation that the input process the recorded memories cognitively, this observation phase brtujuan children can undergo a preliminary understanding of the concept of motion. Lumaksono come to the show arena, Sembahan ( Atur Sugeng), Atur Pambagyo, Minang (Silat), Pemuda Tanon , Olah Rogo And Lumaksono Muncur Beksan; and internalization directly in training and is intended for children pementasan.tahap can directly practice all memorized and dance with the correct technique; as well as the evaluation process is usually done by the parents of dancers nyantrik Mask Dance Ayu by providing intelligent feedback on their performances. The position of children who Nyantrik dancers behind the core, so that the apprentice dancer can make direct observation. Cultural Inheritance Process It needs an understanding and cooperation between the personal, the environment.